Bone Marrow Transplantation Under Regulatory T Cell Cover to Induce Donor-Specific Tolerance. Issue 2 (February 2017) - Hill, Geoffrey R.
Abstract : A commentary on Duran-Struuck et al who describe the in vitro conditions for expanding Treg, and their ability, with CD40L inhibition and cyclosporin A, to promote multi-lineage chimerism and tolerance to renal allografts in nonhuman primates.